(untitled) (CIPEEX, 2025)
Adhesion failures between orthodontic appliances and tooth enamel are common and occur more frequently in posterior teeth. An additional layer of orthodontic adhesive at the interface between the tooth and the occlusal surface of the accessory appears to be a promising maneuver, but the results are controversial. The aim of this study was to compare the shear bond strength (SBS) of orthodontic tubes bonded to tooth enamel following three different protocols. Forty-five bovine incisors were randomly divided into three groups: Group 1 – Transbond XT without reinforcement (control group); Group 2 – Transbond XT + reinforcement with Grandioso Heavy Flow flowable resin; and Group 3 – Transbond XT + reinforcement with conventional Forma resin. The specimens were subjected to a shear test using a universal testing machine with a knife blade tip and a speed of 0.5 mm/min. The shear strength was higher in Group 2 when compared to Group 1. There was no statistically significant difference when comparing Groups 1 and 3, or 2 and 3. The RUC was higher in Group 2 when compared to Group 1. Reinforcement with flowable resin increases the RUC when compared to conventional bonding.